The Kapok (Ceiba sp.) like indicator of origin of atmospheric pollution, in Chaclacayo District, Lima, Perú - Blanco Obregón, Jaziel Martín (2017)
The kapok (Ceiba sp.) Produces a fruit containing cotton-like fluff, which serves as a qualitative indicator of ambient air quality, due to the color that it acquires when exposed to the various particles in the environment.Kapok fluff was used, between the 2nd and 9th blocks of Nicolás Ayllón avenue in Chaclacayo, and complemented with samples from other areas of Lima.In 2008, the differences between the concentrations of lead in soil and cotton-like fluff indicated that this element comes mostly from the combustion motors of vehicles. Points with heavy traffic reported higher levels of Pb, not ruling out the presence of other particulates in the atmosphere.In 2016, the lower values in the fluff and soil, indicate that the reduction of lead as an additive in fuel affects the values of this mineral in the kapok fluff in Chaclacayo. The higher concentration of lead in the soil compared to the concentration in the kapok flufd indicates that the latter gets saturated with Pb.